Exploratory Study Of Micro, Small And Medium Enterprises Profile Of Herbal Product Classification In Banyuwangi Regency - Suwarso Suwarso; Fandi Ahmad; Galih Satriyo (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The purpose of this study is to clearly understand the profile of Micro, Small, and Medium Enterprises (MSMEs) classified as herbal products in Banyuwangi. Furthermore, the purpose of this study is to identify the problems faced by these entrepreneurs and the efforts made to overcome these problems. The approach used in this study is descriptive qualitative. The population in this study is micro, small, and medium-scale entrepreneurs classified as herbal products in Banyuwangi. The sample in this study is producers of herbal products in Banyuwangi who are still actively running their businesses. The data analysis method used is to process data in depth with data from observations, interviews, and literature. Data analysis techniques are carried out by summarizing, categorizing, and interpreting. The results of the study show that the profile of small, micro, and medium enterprises in Banyuwangi Regency shows that MSMEs in the classification of herbal products in Banyuwangi Regency on average start their businesses with their own capital. The number of employees involved in their activities ranges from 2-5, with a monthly turnover of between Rp 8,000,000 and Rp 80,000,000. The products produced by this herbal business in Banyuwangi include beverages, food, and medicines or herbal medicine. Information obtained from informants indicates that sales have increased by 30%-75% during the COVID-19 pandemic. The current challenge is the high cost of production. Financial support is also essential for expanding production scale. Difficulties in obtaining permits are considered very burdensome for business owners, hindering the expansion of marketing activities.